Role of Reservation in Women Empowerment in Haryana Panchayati Raj Institutions - Pooja; Dr. Ashok Kumar Yadav (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2021)
The democratic governance system has developed as the most popular governance system in the modern era, democratic governance system has been adopted in most countries of the world. Under the democratic governance system, it is possible to ensure the participation of common people in governance without any discrimination, which is not possible in any other governance system in such a wide way. The assured participation of the common people in the democratic governance system is not only an indicator of the success of democracy, but it is also important from the point of view of the convenience of governance. The local government system is accepted as a major link to ensure the participation of common people in democracy. Recognizing the importance of the local governance system in Indian democracy, emphasis was laid on the adoption of the local governance system under policy-directive elements in the constitution, which became legally effective in the form of the Panchayati Raj system under the 73rd Constitutional Amendment Act. In the Panchayati Raj system, it was expected to ensure the participation of common people without any discrimination, but due to gender discrimination for centuries, women in India were kept away from governance power, but according to the basic ideals of democracy, freedom, and equality, women in governance power Provision for reservation has been made constitutionally to ensure equal participation of men, so that women can also strengthen the roots of democracy by their participation in governance. Under the Haryana Panchayati Raj Act, of 1994, a provision for reservation has been made for women under the 73rd constitution. The provision of reservation has definitely increased the participation of women in Panchayati Raj Institutions at the local level and women empowerment has been able to get direction.